The own-race bias in child and adolescent witnesses: Evidence from video line-ups - Havard, Catriona (International journal of police science & management, 2017)
This study investigated the own-race bias in British school children using an eyewitness paradigm. Some 319 participants viewed films of two similar staged thefts, one that depicted a Caucasian culprit and the other an Asian culprit, and then after a delay of 2-3 days, viewed a line-up for each culprit. One hundred and seventy-six of the participants were Caucasian and 143 were Asian. There were also two age groups: 164 were aged 7-9 years and 152 were 12-14 years. There was a significant own-race bias for Caucasian participants from both age groups that resulted in more correct identifications for the own-race culprit from target present line-ups and more false identifications for the target absent line-ups. Asian participants from both age groups showed no own-race bias and performed equally accurately for culprits of both races. Measures of inter-racial contact were associated with correct responses for other-race targets and revealed that the majority of Caucasian participants in the current sample had very little contact with Asians, whereas the majority of Asian participants had high levels of contact with Caucasians.